2007
DOI: 10.1111/j.1551-2916.2007.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Ionic Conductivity of Apatite‐Type Lanthanum Silicates Doped With Cations

Abstract: The oxide ion conductivity of apatite‐type lanthanum silicates has been enhanced by cation doping into both La and Si sites. The Sr and Nd fill vacancies on the La site by creating excess oxide ions and increasing the conductivity. Al and Mg, which substitute for Si at a fixed oxygen content, result in an enhancement of conductivity, accompanied by lattice enlargement. The Mg‐doped lanthanum silicate, La9.533(Si5.7Mg0.3)O26, has been shown to have the highest conductivity of 4.4 × 10−2 S/cm at 800°C. The condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 20 publications
6
81
0
2
Order By: Relevance
“…In particular, previous work has shown that for the series, La 8+x Sr 2-x Si 6 O 26+x/2 , the 29 Si NMR spectrum for x=0 has a single peak at δ≈-77 ppm, while for x>0, a second peak is observed at δ≈-80 ppm, attributed to a silicate unit neighbouring an interstitial site [17,27]. In contrast the nitrided samples showed no evidence for this second peak in the sample with x=0.5, while for the x=1 sample, the peak intensity was greatly reduced [8].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, previous work has shown that for the series, La 8+x Sr 2-x Si 6 O 26+x/2 , the 29 Si NMR spectrum for x=0 has a single peak at δ≈-77 ppm, while for x>0, a second peak is observed at δ≈-80 ppm, attributed to a silicate unit neighbouring an interstitial site [17,27]. In contrast the nitrided samples showed no evidence for this second peak in the sample with x=0.5, while for the x=1 sample, the peak intensity was greatly reduced [8].…”
Section: Resultsmentioning
confidence: 99%
“…In order to gain information about the location of the N in the structure, 29 Si NMR data were measured for the La 8+x Sr 2-x Si 6 O 26+x/2 samples after heating at 800 ○ C in ammonia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations